2006
DOI: 10.1051/lait:2006022
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical analysis of casein solubility in water-ethanol solutions

Abstract: -Due to the change in the apparent acid dissociation constant, when ethanol was added to water solutions of an industrially produced spray-dried sodium caseinate, the solution's pH increased proportionally to the reciprocal relative dielectric constant (1/ε). The pH increased by 1 unit when the ethanol volume fraction reached about 0.60. The casein solubility profile at 20 °C as a function of pH (3-8) and the ethanol volume fraction (0-0.75) was quite well represented by the equation describing the ionisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 60 publications
4
14
0
1
Order By: Relevance
“…Additionally, as the relative dielectric constant was lowering by adding ethanol, the pH of the aqueous ethanol was significantly higher when the ethanol concentration was higher (Mezdour et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, as the relative dielectric constant was lowering by adding ethanol, the pH of the aqueous ethanol was significantly higher when the ethanol concentration was higher (Mezdour et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Mart ınez et al (2010) reported the formation of small amounts of formic acid and acetic acid in the hydrolysate of orange peel waste by SCWE at 140 2 160C. Additionally, as the relative dielectric constant was lowering by adding ethanol, the pH of the aqueous ethanol was significantly higher when the ethanol concentration was higher (Mezdour et al 2006).…”
Section: Solid Loss Ph and Yieldmentioning
confidence: 99%
“…A reação de coagulação induzida pelo etanol é um processo de precipitação isoelétrica dependente da quantidade de cargas existentes nas camadas externas das proteínas que compõem as micelas de caseína (Mezdour et al, 2006). A precipitação das micelas de caseína é dependente do perfil de pH, dos componentes iônicos, como metais bivalentes, especialmente íons cálcio que interferem na estabilização estérica do meio, e da constante dielétrica (Tsioulpas et al, 2007).…”
Section: Materiais E Métodosunclassified
“…with z being the amount of charged residues and pk a the acid constant (Mezdour et al, 2006). The activity γ was estimated as 1, a simplification that is admissible for dilute systems.…”
Section: Charge Of Used Cnmentioning
confidence: 99%
“…Surface tension was measured by the du Noüy ring method at concentrations between 10 −3 and 10 −7 mol/L as function of time t, until an equilibrium value γ eq ( ) was reached. The γ eq values of dialyzed and nondia- Mezdour et al (2006) by using the amino acid sequence of the named genetic types published by Ng- Kwai-Hang (2004) and the acid and basic dissociation constants published by Walstra (2003).…”
Section: Surface Propertiesmentioning
confidence: 99%